GAME-BASED LEARNING AND STUDENT ENGAGEMENT: EXPLORING THE ROLE OF AI IN EDUCATIONAL GAMES - Mohammad Ariswara Rai Djafar; Dilshan Parera; Lamsike Pateda (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2026)
Game-based learning (GBL) has emerged as an innovative approach to engage students and enhance learning outcomes. With advancements in artificial intelligence (AI), educational games are increasingly capable of providing personalized learning experiences. This study investigates the role of AI in GBL and its impact on student engagement and academic performance. The research aims to evaluate how AI-powered educational games influence student motivation, retention, and interaction with learning materials. A mixed-methods approach was employed, combining quantitative assessments of student performance and qualitative feedback from students and educators. The findings indicate that AI-enhanced educational games significantly increase student engagement, with an observed 25% improvement in participation and a 20% increase in academic achievement. Students reported higher levels of motivation, while teachers noted improved performance in both individual and group learning contexts. These results suggest that AI-driven personalization within educational games can effectively address individual learning needs, making learning more interactive and adaptive. The study concludes that while AI-powered games are a promising tool for enhancing education, they must be integrated with traditional teaching methods to maintain the essential human connection in the learning process. Future research should focus on the long-term effects of AI in GBL and explore the ethical considerations surrounding data privacy and AI biases.